FISCAL POLICY AND THE CURRENT ACCOUNT DYNAMICS IN SUB SAHARAN AFRICA (2013)
The Current Account Balance (CAB) of Sub-Sahara African (SSA) countries is characterised by persistent deficits, averaging -7.3%, -3.4%, and -2.4% as a percentage of Gross Domestic Product in 1981, 1995 and 2009, respectively. While there is a growing body of empirical literature on the determinants (focusing specifically on Real Exchange Rate (RER), external debt, Terms of Trade (TOT), among others) of deficit in the CAB, little attention has been devoted to the role of fiscal policy (FP). This study, therefore, examined the effects of FP (measured by government expenditure) on the CAB in 34 SSA countries covering the period between 1985 and 2009. A dynamic open-economy model, predicated on an inter-temporal framework that considered the CAB as national savings (borrowing) vis-á-vis the rest of the world and as the outcome of the inter-temporal choices of households, firms and governments, was estimated with data from World Development Indicators. The model combined the effects of FP and other determinants as control variables (RER, external debt and TOT) on dynamic adjustments of the CAB. The system Generalised Method of Moments estimation (GMM) technique that took cognizance of feedback mechanisms, retained valuable information and controlled for the joint endogeneity of FP and other determinants in the presence of country-specific effects was employed. A Panel Vector Autoregressive (PVAR) model was estimated to quantify the adjustment path of the CAB to FP shocks with reference to impulse response functions and variance decompositions. Diagnostic tests (Hansen, PVAR stability condition and residual normality tests) were carried out to ascertain the robustness of the parameter estimates. Expansionary FP significantly led to a deterioration of the CAB, through its effects on aggregate income and imports. The coefficient of government expenditure was -0.2, indicative of an inverse change in the CAB of up to one-fifth of any change in government expenditure, while the coefficient of TOT (0.01) implied approximately one-hundredth of the effect of a change in TOT on the CAB. The coefficient of external debt showed that when it increased by 10.0%, the CAB improved by 0.2% and the same percentage depreciation in RER improved it by 25.0%. These coefficients were statistically significant at the 5% level. The dynamic response of the CAB to a generalised one standard deviation increase in government expenditure was a deterioration of 0.9% in the first year and the effect fell rapidly to 0.5% and 0.2% in the third and sixth years, respectively. This implied that the CAB did not fully recover to its initial value after the sixth year. In the same years (first, third and sixth), variations in the CAB were largely explained by its own innovations, which were 82.2%, 78.1% and 73.7%, while FP accounted for 3.5%, 3.1% and 2.8% of its variations. Government expenditure significantly influenced the behaviour of the current account balance in sub-Sahara African countries. Accordingly, fiscal policy is important in the restoration of equilibrium in the external sector. Therefore, the government should restrain rapid increases in its expenditure in order to check balance of payments deficits.